Clinical Forensic Assessment of Victims with Stab Wound - Prabowo, Yudha Erik; Suryanegara, I Ketut Heru; Perwira, Satria; Yudianto, Ahmad (UNUSA Press, 2024)
Introduction: Violent crimes using sharp objects are a common problem in Indonesia because sharp weapons can be easily accessed. When evaluating sharp-force injuries, the correct interpretation of the morphology of individual wounds, as well as the overall pattern of findings, is of paramount importance in the reconstruction aspect of the crime. Any knowledge of the occurrence and distribution of sharp force injuries in knife attack victims and perpetrators can help to verify statements or expose defensive lies. Case: We present, a patient from another hospital came to the emergency room at Doctor Soetomo Hospital with a stab wound to the right chest. The 35-year-old male victim, with the initials SPJ, admitted that he was stabbed by his brother. The victim's vital signs were stable when examined. On the right chest, an open wound with flat edges and sharp and blunt angles was found, measuring three centimeters long and five centimeters wide. The victim underwent radiological and laboratory examinations, installed water-sealed drainage, and was administered anti-pain and antibiotics. Discussion: The qualification for this patient's wound based on the Indonesian Criminal Code and the scoring carried out is a moderate wound Conclusions: Based on the law and the scoring carried out by the author, the wounds on the patient's body are injuries resulting from a criminal act and are included in the category of moderate abuse, which means that the injuries that occurred to the victim did not cause death or cause permanent disability but caused temporary obstacles in carrying out work.